THE IMPORTANCE OF PRECAUTIONARY SAVING MOTIVE AMONG INDONESIAN HOUSEHOLDS - Ahmad Zafarullah Abdul Jalil (Faculty of Economics and Business, Universitas Gadjah Mada, 2009)
In the developing world, the population is frequently faced with numerous natural, economic, institutional and market risks. Because of these uncertainties, many individualsand households experience difficult periods of unexpected reduction in income. Using panel data from the Indonesian Family Life Survey (IFLS), this paper tests the existence ofprecautionary saving associated with income risk in Indonesia. The results of the estimation show that the uncertainty variable is not significantly related to the growth of consumption which signifies that Indonesian households do not constitute precautionary saving to smooth their consumption. The finding may be explained by the fact thatIndonesian households have in their possession other type of support mechanisms based particularly on inter-generational and -communal solidarity.Keywords: uncertainty, income risks, precautionary savings, consumption smoothing.